2016
DOI: 10.1186/s13063-016-1445-7
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive intraocular and peri-ocular steroid (triamcinolone acetonide) versus standard treatment in eyes undergoing vitreoretinal surgery for open globe trauma (ASCOT): study protocol for a phase III, multi-centre, double-masked randomised controlled trial

Abstract: BackgroundEyes sustaining open globe trauma are at high risk of severe visual impairment. Ocular injuries which result in visual loss invariably affect the posterior segment of the eye, and prevention of visual loss involves posterior segment (vitreoretinal) surgery. Despite improvements in vitreoretinal surgical techniques, outcomes in these patients remain unsatisfactory, and development of the intraocular scarring response proliferative vitreoretinopathy is the leading cause. Proliferative vitreoretinopathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Furthermore, replacing anatomic primary outcomes with a visual outcome seems to be a plausible design for future vitreoretinal clinical trials and is strongly advocated by patient groups involved in protocol development. 12,47,48 Overall, we observed a higher number of AEs in the control group. There were fewer cases of postoperative uveitis in the adjunct group, perhaps indicative of the additional anti-inflammatory activity of the dexamethasone.…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, replacing anatomic primary outcomes with a visual outcome seems to be a plausible design for future vitreoretinal clinical trials and is strongly advocated by patient groups involved in protocol development. 12,47,48 Overall, we observed a higher number of AEs in the control group. There were fewer cases of postoperative uveitis in the adjunct group, perhaps indicative of the additional anti-inflammatory activity of the dexamethasone.…”
Section: Discussionmentioning
confidence: 53%
“…Though there is one study designed to compare periocular steroid injections undergoing PPV in OGI 12. The mentioned study has not reported a conclusion about this issue yet 12. Even though high-dose therapy was not administered to the present subjects, this treatment approach in severely injured eyes is not supported by the reliable evidence and additional randomised clinical trials are needed.…”
Section: Discussionmentioning
confidence: 83%
“…Some authors recommend high-dose systemic steroids (eg, acute spinal cord injury)9 10 but some authors do not (eg, traumatic optic neuropathy)11 in a patient with trauma. Though there is one study designed to compare periocular steroid injections undergoing PPV in OGI 12. The mentioned study has not reported a conclusion about this issue yet 12.…”
Section: Discussionmentioning
confidence: 98%
“…As an example, we consider the Adjunctive Steroid Combination in Ocular Trauma (ASCOT) trial, a pragmatic, double-blind, multi-centre randomised controlled trial testing whether adjunctive steroid (triamcinolone acetonide), given at the time of surgery for open globe trauma can improve the outcome of surgery [13]. Adults undergoing vitrectomy for open globe trauma were randomised to receive adjunctive intraocular and periocular steroid or standard treatment (no steroid) during surgery in a 1:1 ratio.…”
Section: The Ascot Trialmentioning
confidence: 99%